DETERMINANTS OF FIRM VALUE: EVIDENCE FROM CAPITAL STRUCTURE AND PROFITABILITY (CASE STUDY OF PT NIPPON INDOSARI CORPINDO TBK 2015–2024 - Nina Shabrina; Rosalina Wati Tias (Jurnal Ilmiah Ekonomi Manajemen & Bisnis, 2026)
Firm value is a critical indicator of corporate performance; however, empirical evidence on the determinants of firm value—particularly in the Indonesian food and beverage sector—remains inconclusive. Prior studies have reported mixed findings regarding the effects of capital structure and profitability on firm value, suggesting the need for further investigation in a single-firm longitudinal context. This study aims to address this gap by providing empirical evidence on the partial and simultaneous effects of Debt to Asset Ratio (DAR) and Return on Asset (ROA) on Firm Value at PT Nippon Indosari Corpindo Tbk over the period 2015–2024. The population of this study is PT Nippon Indosari Corpindo Tbk, with samples determined through purposive sampling. The research employs a quantitative descriptive method, with data tested using classical assumption tests—including normality, multicollinearity, heteroscedasticity, and autocorrelation tests—followed by correlation and determination tests, multiple linear regression analysis, partial test (t-test), and simultaneous test (F-test), processed using Eviews 12. The results indicate that partially, DAR has a significant effect on Firm Value, while ROA does not. However, the simultaneous test (F-test) confirms that DAR and ROA jointly have a significant effect on Firm Value. This study contributes to the literature by demonstrating that capital structure, proxied by DAR, is a more dominant determinant of firm value than profitability in the context of a leading Indonesian food manufacturer, offering practical implications for managerial decision-making related to financing policy